alpha-amylase from five strains of Bacillus amyloliquefaciens: evidence for identical primary structures. - Borgia, P T (1978)
The alpha-amylases from five strains of Bacillus amyloliquefaciens were compared to determine whether differences in primary structure are responsible for variations in catalytic properties previously reported among the enzymes. Amino acid analysis established virtually identical compositions for the proteins. Reaction with dimethylaminoaphthylene sulfonylchloride indicated the amino-terminal amino acid of each amylase to be valine. Carboxyl termini of the enzymes have been determined by digestion with carboxypeptidase A. The resulting kinetic data indicate tyrosine as the carboxyl terminus and leucine as the penultimate residue for all five proteins. Isoelectric focusing of the enzymes yielded isoelectric points in the pH range of 5.09 to 5.18. Tryptic digests of the enzymes chromatographed on a cation-exchange column showed identical elution patterns. It is concluded that the primary structure of the amylase from the five strains is identical or exhibits only conservative substitutions.